(untitled) (Journal of Engineering, 2008)
Solar radiation is one of the renewable energy resource that can be used in different fields such as heating, cooling & lighting to employ the double use of passive and active systems’ that integrate with the ideal mass grouping, direction,layout & design of building form and its envelope correctly, by the integration ofthese tools and trends with each others in away that insures energy conservation andlessen the use of fossil fuel in buildings to achieve environmental balancing.In order to explain the point of view for the process of environmental design &sustainable building that include (planning & mass grouping) to work as integrated system to design efficient energy buildings where the site and setting, planningexternal form, and internal organization as well as storage mechanism, cooling heating and lighting to get best result in order to conclude the relationship between mass grouping, set and layout of the site including all processes that act as bases of environmental design and its relation with thermal comfort and controlling solar (loss & gain) as a goal for internal thermally comfortable environment, visually & biologically, by using renewable energies in residential complexes in hot dry condition